Memahami Androgogi dan Pedagogi: Pendekatan Efektif dalam Membimbing Pembelajaran Orang Dewasa - Hasanbasri Hasanbasri; Parisyi Algusyairi; Nurhayuni Nurhayuni; Afriza Afriza (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2023)
The purpose of writing this work is to determine the differences, applications and strategies of androgogy and pedagogy in the context of adult learning. This research uses a literature review method by collecting data sources from various academic sources to understand the differences and effectiveness of andragogy and pedagogy in adult education. Data were analyzed qualitatively to formulate a comprehensive understanding of the two approaches. The results of this work are a) The main difference between andragogy and pedagogy is the learning orientation, where andragogy focuses on students, while pedagogy focuses more on the role of the teacher. Understanding these differences is important in choosing a learning approach. b) the need to develop a more holistic approach to adult education that combines elements of andragogy and pedagogy, taking into account individual needs, creativity and available resources. c) The application of the spiritual andragogy approach increases the motivation and learning outcomes of adult students, but weaknesses arise because adult students have difficulty choosing learning materials according to their interests.